Pengaruh Brand Image, Service Quality dan Perceived Value Terhadap Brand Loyalty (Studi Kasus: Mahasiswa STP Trisakti) (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2015)
Universities need good branding and nonstop effort to exist in this tight competition, not to mention foreign universities also promoting their institutions to attract new students in Indonesia. Universities need to know the condition of their brand image, service quality given, and perceived value taken by the students, so the effects of student loyalty may be identified, and then fulfill the needs and wants of students which eventually recommend others of their university and will lead to positive WOM. This research was made to achieve the purpose of identifying the effects of brand image (XI), service quality (X2), and perceived value (X3) towards brand loyalty (Y) from students of Trisakti Institute of Tourism. The research models used are descriptive and associative models, using the help of SPSS V.21. This research uses the random sampling technique to take samples, with the total number of 94 students. The instruments used as a measure in this research are questioners which consist of 46 statements. The variables used are brand image (X1), service quality (X2), and perceived value (X3), simultaneously effects the brand loyalty (Y) with p-value in column sig 0,000 and 0,000 < 0,05 level of significant, with a value of Fcount (31.268) > Ftable (2.71). From this research comes a conclusion which Trisakti Institute of Tourism as the reputable tourism university in Indonesia needs to sustain its fine image and increase service quality which can satisfy students and maintain its quality as a featured tourism university.